THE EFFECT OF SERVICE QUALITY, PRICE, AND LOCATION ON CUSTOMER SATISFACTION AT ALIB CAR WASH IN MUARA BULIAN - Ahmad Fithoni; Irfan Widyanto; Doni Prasetya (Yayasan Education and Social Center, 2023)
Customer satisfaction is the level of satisfaction or satisfaction felt by customers after they use a company's product or service. It reflects a customer's subjective evaluation of their experience and the degree to which their expectations were met. Customer satisfaction has a significant impact on business success. Therefore, companies often try to increase customer satisfaction by understanding and meeting their needs and expectations, improving product or service quality, providing good customer support, and maintaining effective communication with customers. The purpose of this study was to explain the effect of service quality, price and location on customer satisfaction at the Alibdi Muara Bulian Car Wash. The analytical method used is a quantitative method using multiple linear regression analysis. The results of this study resulted in the results of testing the hypothesis on the effect of the price variable on customer satisfaction that the value of Tcount (5,993) > Ttable (1.986) based on the comparison of Tcount and Ttable face H2 accepted means the price (X2) has a significant effect on customer satisfaction (Y). The results of testing the hypothesis on the influence of service quality, price, and location variables on customer satisfaction show that the value of f is obtained by a ftable value of 2.71 while the value of fcount is 91.267 and the significance value is > 0.05, so H4 being accepted means that it is proven that there is a joint and significant influence of service quality, price, and location on customer satisfaction. R2 determination test shows that the combination of service quality, price, and location variables together contributes 74.4% to customer satisfaction while the remaining 25.6% is the contribution of other variables not examined in this study